A rationalised virological electron microscope specimen testing policy. PHLS North West Viral Gastroenteritis and Electron Microscopy Subcommittee. Issue 6 (1st June 1999) - Curry, A; Bryden, A; Morgan-Capner, P; Fox, A; Guiver, M; Martin, L; Mutton, K; Wright, P; Mannion, P; Westwell, A; Cheesbrough, J; Ashton, I; et al.
Abstract : The aim of this project was to produce guidance for a rationalised virological electron microscopy specimen testing policy for PHLS North West, to facilitate centralisation of a groupwide diagnostic electron microscopy service on a single site. Careful specimen selection to limit numbers and the groupwide use of commercially available enzyme immunoassays has allowed PHLS North West to reduce the number of specimens prepared for electron microscopy. The rationalised virological electron microscopy specimen testing policy has enabled a diagnostic electron microscopy service to be provided from a single site with a manageable workload. Implementation of this specimen testing policy by PHLS North West has been successful and may be applicable to other laboratories (or groups of laboratories) to maximise the use of expensive electron microscopy facilities.